The COVID-19 pandemic and nurses' attitudes toward death - Maria Filomena Passos Teixeira Cardoso; Maria Manuela Ferreira Pereira da Silva Martins; Letícia de Lima Trindade; Olga Maria Pimenta Lopes Ribeiro; Esmeralda Faria Fonseca
Objective: to analyze nurses' attitudes toward death in a hospital context after the critical period of the COVID-19 pandemic in Portugal. Method: this quantitative, descriptive, exploratory study was conducted in a university hospital and addressed 995 nurses. Revised Death Attitude Profile (DAP-R) was used to collect data, which were analyzed using analytical and inferential statistics. Results: the nurses most frequently agreed with the statements concerning the Neutral/Neutrality Acceptance and Fear. Age, marital status, profession, and unit of work influenced the nurses' attitudes toward death. During the critical pandemic period, the nurses providing care to patients with COVID-19 presented the following means: Fear (28.89/±8.521) and Avoidance Acceptance (18.35/±7.116), which were higher than the mean obtained in the Escape Acceptance dimension, with significant differences (p=0.004). Conclusion: the nurses held Fear and Avoidance attitudes, revealing the need to qualify and support Nursing workers to cope with the death of those they provide care and manage pandemics and catastrophes.